Analisis Respon Konsumen Terhadap Antrean Yang Terjadi Di SPBU 3440506 Cipatik Kecamatan Cihamplas Kabupaten Bandung Barat - Ageng Kanda Saepudin S; Rian Abdul Rohman (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze consumer responses to the queue phenomenon that occurs at Cipatik Public Fuel Filling Station (SPBU). Queues at gas stations are often a major concern for consumers, affecting customer satisfaction and the operational performance of gas stations. This study identifies the main factors that influence consumer response to queues, focusing on queue cases, waiting time, and consumer feelings regarding service. The research method used a quantitative approach through a consumer survey involving a representative sample of Cipatik gas station users. Data was collected through a questionnaire covering aspects such as consumer perception of service speed, queue efficiency, and overall satisfaction level. The results of data analysis show that there is a lack of consumer satisfaction with the queues that occur at Cipatik Service Station, West Bandung Regency. Therefore, it is necessary to improve queue management by the gas station. The addition of filling pump lines needs to be addressed so that the service level can increase. In addition, shorter waiting times and a more efficient service experience are considered by consumers as key factors in increasing their satisfaction. The findings of this study provide valuable insights for Cipatik Service Station management and relevant stakeholders to improve queue management and increase customer satisfaction. The practical implications of this study can assist policy makers in developing more effective operational strategies to address queuing issues and improve consumer experience at the gas station.